2012
DOI: 10.2478/v10019-012-0042-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiple brain metastases - current management and perspectives for treatment with electrochemotherapy

Abstract: Background. Due to the advanced oncological treatments of cancer, an overall increase in cancer incidence, and better diagnostic tools, the incidence of brain metastases is on the rise. This review addresses the current treatment options for patients with multiple brain metastases, presenting electrochemotherapy (ECT) as one of the new experimental treatments for this group of patients.Conclusions. Neurosurgery, stereotactic surgery, and whole-brain radiotherapy are the evidence-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 51 publications
0
28
0
1
Order By: Relevance
“…1,3 Novel electrodes were designed to use electrochemotherapy for brain tumors, 27 colorectal cancer, 28 bone 29 and liver 30 metastasis, soft tissue sarcoma, etc. The bladder is relatively easy to access.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Novel electrodes were designed to use electrochemotherapy for brain tumors, 27 colorectal cancer, 28 bone 29 and liver 30 metastasis, soft tissue sarcoma, etc. The bladder is relatively easy to access.…”
Section: Discussionmentioning
confidence: 99%
“…The electric field is caused by high-voltage electric pulses that are delivered to the target tissue (i.e., tumor) using electrodes (Mir et al 1991). ECT is already used in clinical practice for treating metastases of skin melanoma in more than 100 clinical institutions in Europe ) and has already been introduced to clinical trials for treating deep-seated metastases in the liver (Edhemović et al 2011), brain (AgerholmLarsen et al 2011;Linnert et al 2012;Mahmood and Gehl 2011), bone (Fini et al 2011) and soft tissue (Neal et al 2011). While following standard operating procedures (Mir et al 2006) ensures safe and successful treatment of skin melanoma metastases (Marty et al 2006), patient-specific treatment planning is nevertheless required for ECT of deep-seated tumors (Pavliha et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, the configuration of the electrodes is a technological feature that is fast developing and now different sets of electrodes are used for specific administrations long-needle single electrodes for metastases of colorectal tumors in the liver 25 , bone metastases 7 , soft tissue sarcoma 26 , endoluminal electrodes for colorectal, gastric and esophageal tumors 27 and expandable ''umbrella'' type electrodes for brain tumors 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ECT is used in several clinical studies treating tumor metastases in the brain 8 , bone 9 and liver 10 . Clinical studies in veterinary oncology have already demonstrated that ECT treatment results in up to 80% longlasting objective responses when treating cutaneous and subcutaneous tumors in dogs 11,12 , cats 13 and horses 14 .…”
Section: Introductionmentioning
confidence: 99%